Development and Evaluation of Near‐Real Time TEC and Ancillary Products for SANSA Space Weather - Tshimangadzo M. Matamba; Donald W. Danskin (Space Weather)
Abstract In this paper, the second version of SANSA's Total Electron Content (TEC) maps is presented with its associated methodology and assumptions. The method is based on Ma and Maruyama (2003, https://doi.org/10.5194/angeo-21-2083-2003) determination of receiver bias and hence TEC for individual receivers. By combining values of slant TEC from 20 South African Trignet stations, maps of TEC, spatial gradient of TEC and temporal gradient of TEC can be determined. Quality factors and error of fit are determined for each map and are analyzed to identify the level of validity for TEC maps. In addition, the first operational estimation of TEC gradients both temporal and spatial are presented and discussed for the 4–5 November 2021 negative ionospheric storm. The TEC from the maps shows good agreement with the ionosonde TEC and AfriTEC model.